Hiding Information using Replacement in Silent Mutation of DNA Sequences - Sadoon Abdullah; Ahmed Nori (Al-Rafidain Journal of Computer Sciences and Mathematics)
The present study included an application of new method of steganography using DNA sequence as a media for hiding. This method is considered a secret cover for the secret message (text, image), avoid attention of unauthorized person in addition to be inextricable since it needs high effort, long time and well background in biology. Hiding secret message in a known DNA sequence belongs to prokaryotic organism was conducted. The DNA sequence obtained from EBI location (European Bioinformatics Institute). Among the DNA molecule characters, one of the mutant ability types, that is the silent mutant, was choose to hide a secret message within the sequence. Then the sequence with the hidden message was sent to receiver via many methods. For more precaution the DNA sequence with the message was hide as a colored image with different dimensions and extension (BMP, PNG). However, image quality remain unchanged. Results of study revealed high hiding ratio.